Targeting Conventional Dendritic Cells to Fine-Tune Antibody Responses - Tesfaye, Demo Yemane; Gudjonsson, Arnar; Bogen, Bjarne; Fossum, Even (Frontiers in Immunology, 2019)
Dendritic cells (DCs) facilitate cross talk between the innate and adaptive immune system. They sense and phagocytose invading pathogens, and are not only capable of activating naïve T cells, but can also determine the polarization of T cell responses into different effector subtypes. Polarized T cells in turn have a crucial role in antibody class switching and affinity maturation, and consequently the quality of the resulting humoral immunity. Targeting vaccines to DCs thus provides a great deal of opportunities for influencing the humoral immune responses, by fine-tuning the T cell response as well as regulating antigen availability for B cells. In this review we aim to outline how different DC targeted vaccination strategies can be utilized to induce a desired humoral immune response. A range of factors, including route of vaccine administration, use of adjuvants, choice of DC subset and surface receptor to target have been reported to influence the resulting immune response and will be reviewed herein. Finally, we will discuss opportunities for designing improved vaccines and challenges with translating this knowledge into clinical or veterinary medicine.